Late Roman wares from Marea B at Alexandria (Egypt) - Shaaban, Amany (Rei Cretariae Romanae Fautorum Acta, 2024)
In 2018, The Ministry of Tourism and Antiquities executed rescue excavations at an archaeological site in the western part of Marea abbreviated Marea B, located approximately 700 m from Hauwâriya, West Alexandria. That site constituted an important stopover for the pilgrims who used to come from all sides to visit the tomb of Saint Menas. The excavations uncovered several chambers and structures, and an assemblage of pottery dating to the late Roman and early Byzantine periods. This paper focuses on studying and dating different categories of pottery found during the excavation. These include different types of local production, such as some Late Roman Amphora 1, many examples of Late Roman Amphorae 5/6, some rare Late Roman Amphorae 7, tableware, cooking ware and some fine Egyptian red slipware.